2020
DOI: 10.7241/ourd.20202.5
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling for androgenetic alopecia not responding to conventional treatment

Abstract: Microneedling appears to be appealing treatment of androgenetic alopecia (AA). We report five cases of androgenetic alopecia that were treated with microneedling along with oral finasteride and minoxidil, as a first case series from Nepal. Most of them showed moderate to greatly increase in hair growth with satisfaction score of more than 75% without any complications. This case series highlights the importance of considering microneedling as one of the treatment choice for hair growth in patients with AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…5 Electric microneedle, a minimally invasive treatment technique, is a thin needle used to pierce the epidermis and the superficial layers of the dermis on the scalp, which could physically disrupt the stratum corneum of the skin, following by creating temporary and water-laden cavities that facilitate the entry of drug molecules into the epidermis. 6 By impairing the integrity of skin barrier, electric microneedles could induce the separation of keratin-forming cells, thus causing the release of various cytokines 7,8 such as IL-1a, IL-8, IL-6, TNF-A and granulocyte-macrophage colony stimulating factor (GM-CSF). This will further give rise to dilated blood vessels and keratin-forming cell migration, differentiation as well as proliferation in the dermis to repair the damage of the epidermal layer.…”
Section: Introductionmentioning
confidence: 99%
“…5 Electric microneedle, a minimally invasive treatment technique, is a thin needle used to pierce the epidermis and the superficial layers of the dermis on the scalp, which could physically disrupt the stratum corneum of the skin, following by creating temporary and water-laden cavities that facilitate the entry of drug molecules into the epidermis. 6 By impairing the integrity of skin barrier, electric microneedles could induce the separation of keratin-forming cells, thus causing the release of various cytokines 7,8 such as IL-1a, IL-8, IL-6, TNF-A and granulocyte-macrophage colony stimulating factor (GM-CSF). This will further give rise to dilated blood vessels and keratin-forming cell migration, differentiation as well as proliferation in the dermis to repair the damage of the epidermal layer.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were also conducted and yielded equivalent results of increased hair density and thickness 118–121 . Dhurat and Parajuli reported a case series of patients who were poor responders to conventional therapies and gained significant improvement after the addition of microneedling 122,123 124 …”
Section: Adjuvant Therapymentioning
confidence: 77%
“… 118 , 119 , 120 , 121 Dhurat and Parajuli reported a case series of patients who were poor responders to conventional therapies and gained significant improvement after the addition of microneedling. 122 , 123 Jha et al also reported superior clinical outcomes seen in the PRP, microneedling, and topical minoxidil patients vs. monotherapy patients. 124 There is evidence that microneedling preceding PRP enhances the efficacy of PRP as the pinpoint bleeding provoked by microneedling allows more uniform absorption of PRP 125 ; there is lack of standardization in this method of treatment.…”
Section: Adjuvant Therapymentioning
confidence: 97%